From Nature to Innovation: Advances in Nanocellulose Extraction and Its Multifunctional Applications - A. M. P. Hansini; G. D. C. P. Galpaya; M. D. K. M. Gunasena; P. M. Abeysundara; V. Kirthika; L. Bhagya; H. D. C. N. Gunawardana; K. R. Koswattage (Molecules)
Nanocellulose obtained from renewable and abundant biomass has garnered significant attention as a sustainable material with exceptional properties and diverse applications. This review explores the key aspects of nanocellulose, focusing on its extraction methods, applications, and future prospects. The synthesis of nanocellulose involves mechanical, chemical, and biological techniques, each uniquely modifying the cellulose structure to isolate cellulose nanocrystals (CNCs), cellulose nanofibers (CNFs), or bacterial nanocellulose (BNC). These methods provide tailored characteristics, enabling applications across a wide range of industries. Nanocellulose’s remarkable properties, including high mechanical strength, large surface area, thermal stability, and biodegradability, have propelled its use in packaging, electronics, biomedicine, and environmental remediation. It has shown immense potential in enhancing the mechanical performance of composites, improving water purification systems, and serving as a scaffold for tissue engineering and drug delivery. However, challenges related to large-scale production, functionalization, regulatory frameworks, and safety concerns persist, necessitating further research and innovation. This review emphasizes the need for sustainable production strategies and advanced functionalization techniques to harness nanocellulose’s full potential. As an eco-friendly, high-performance material, nanocellulose presents a promising avenue for addressing global sustainability challenges while offering transformative solutions for various industries.